Treatment of unusual locked posterior fracture-dislocation of the shoulder: a case series - Park, Ho Yeon; Kim, Seok Jung; Sur, Yoo Joon; Jung, Jae Woong; Kong, Chae-Gwan (Clinics in Shoulder and Elbow, 2020)
Locked posterior fracture-dislocation of the shoulder (LPFDS) is a very rare injury that occurs predominantly in young patients following high-energy trauma. The long-term outcome of the treatment of this injury is often poor. This study sought to present the characteristics of injury, discuss the pathological anatomy, and to report the treatment outcomes of our case series. Between January 2012 and May 2018, a total of 234 patients who underwent surgical treatment for proximal humerus fractures were reviewed. Among them, six patients (mean age, 54.7 years; range, 35-76 years) with LPFDS were included in this study. Four patients were treated with open reduction and internal fixation (ORIF) with locking plates, one with hemiarthroplasty, and one with reverse total shoulder arthroplasty. Clinical results were evaluated by Constant, American Shoulder and Elbow Surgeons (ASES), and visual analog scale (VAS) scores and radiologic evaluation was conducted using follow-up radiographs. The mean length of follow-up was 26.2 months (range, 12-54). The mean Constant, ASES, and VAS scores were 66.7, 65.5, and 2.2, respectively. Four patients who underwent ORIF achieved bony union, but avascular necrosis (AVN) of the humeral head was observed in two patients. No complications were observed in the patients who underwent arthroplasty surgery until final follow-up. In the treatment of LPFDS, replacement arthroplasty can produce predictable results. The approach of ORIF may be considered as a first choice of treatment in young patients but is sometimes correlated with postoperative complications such as AVN and the functional outcomes may be unpredictable. Therefore, patients should undergo careful diagnosis and treatment of this type of injury.